If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 6 + -9x = 2 + -15 Reorder the terms: 6 + 8x + -9x = 2 + -15 Combine like terms: 8x + -9x = -1x 6 + -1x = 2 + -15 Combine like terms: 2 + -15 = -13 6 + -1x = -13 Solving 6 + -1x = -13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = -13 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = -13 + -6 -1x = -13 + -6 Combine like terms: -13 + -6 = -19 -1x = -19 Divide each side by '-1'. x = 19 Simplifying x = 19
| -6m=-72 | | 3(6-b)-(-5)=-7 | | 42+(-81)+63-(58)-77= | | 7x+7-9x=15-19x+17x-8 | | 6x-7y=16 | | -15=y+15 | | 3-2[5-3(x+1)]=4x-10 | | 6p=p-40 | | (4x^2)+37x+75=0 | | z^2+13z+36=0 | | X^2-8x+84=0 | | 3x-10=2x+18 | | -x-24=5+x | | -18d+5d(8+3d)=7(3d-8) | | 5+r=18 | | 16-9(d-5)=-2 | | -148=4(6+7x)-4 | | c+5=41 | | 24=2x+3(2x) | | 5.8=-8+x | | 6(x+4)-5=1 | | 3+5w=9+4w | | -2x+2=-2x+1 | | 7=n/7+9 | | 2n^2-3n+4=0 | | (9x^2)-131x+450=0 | | -3(y-6)=30 | | 2y+x=-9 | | Y+11=-11 | | 5-x-1=x-2 | | Y+11=11 | | 11=3n-10 |